1963
DOI: 10.1084/jem.118.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Excess Vitamin a on the Embryonic Rat Oesophagus in Culture

Abstract: The effect of excess vitamin A on the oesophageal epithelium of late foetal rats has been studied in organ culture. In explants kept in normal medium the epithelium is, at first, higher and the keratinisation increased as compared with the development of the organ in vivo. At the later stages of growth, the acceleration of keratinisation leads to an extreme thinning of the epithelium. Excess vitamin A completely inhibits keratinisation and induces a transformation of the cells lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…After inflicting wounds by biopsy, marked clones span both proliferative and non‐proliferative zones of the healing oesophageal epithelium, suggesting that they maintain a progenitor fate with distinct phenotypes. With atRA treatment, the authors show that suprabasal cell formation increases, which is consistent with the known effect of atRA on the oesophagus (Lasnitzki, 1963). Statistical analysis reveals that the probability of forming basal and suprabasal cells was not altered with atRA administration.…”
supporting
confidence: 84%
“…After inflicting wounds by biopsy, marked clones span both proliferative and non‐proliferative zones of the healing oesophageal epithelium, suggesting that they maintain a progenitor fate with distinct phenotypes. With atRA treatment, the authors show that suprabasal cell formation increases, which is consistent with the known effect of atRA on the oesophagus (Lasnitzki, 1963). Statistical analysis reveals that the probability of forming basal and suprabasal cells was not altered with atRA administration.…”
supporting
confidence: 84%
“…Such cellular population shifts, either toward excessive mucusproducing strata or into SSE have been abundantly reported in experimental systems. 7, 8,10,12,13,[15][16][17]25 Moreover, various epithelial covered organs such as the tracheobronchial tree, the nose or the vagina, exhibit such changes secondary to infections or vitamin A deficiency.23,25…”
Section: Methods and Matzrlalsmentioning
confidence: 99%
“…Experiments have also shown that keratinization can be inhibited in vitro by the addition of vitamin A to the medium supporting the growth of chick embryo skin (Fell & Mellanby 1953), human fetal skin (Lasnitzki 1958), human adult skin (Szabo 1962), fetal mouse oral mucosa (New 1963), and rat esophagus (Lasnitzki 1963).…”
Section: Discussionmentioning
confidence: 99%